Study of Supreme Court Decision (Number 1666 K/Pdt/2022) Sale and Purchase Agreement Between Budi Said and PT Antam - Briyan Dustin; Gunardi Lie; Moody Rizqy Syailendra P (Journal of Social Science, 2023)
The study of the court verdict number 158/Pdt.G/2020/PN Sby, is a unlawful tort act of Indonesian Civil Law, between Budi Siad as the claimant, and a major mining coroporation owned by the Indonesian Government, ANTAM Ltd, and also with it, are some other individuals who are responsible in the tort. In this court verdict study, the author would like to examine, on what are the constituent of unlawful tort, have the defendant do. Lest we forget also that in a verdict study the author would also like to find out upon what are the factors used bby the judge in judging and considering the verdict of the case. The case itself occurred due to incongruity found between the amount of goods purchased by the claimant and the price paid, the incongurity found resulted in the loss received by the claimant. The purpose of this research specifically is to reinforce the theories used by the court in order to issues the verdict on the defendants. This research also use d normative jurdicial approach and use library study techniques of which the sources came from secondary sources such as books, journals, papers, or newspapers. In which the research method used normative-empirical method. From the said research, the author has found that the unlawful tort act that have been commited by the defendants are fullfield in most elements, and in terms of the second problems formulated in this article the author finds out that the legal findings methode the judge used are juridicialm philosopical, and sociological bases.